Different Evolutionary Origins for the Reach and the Grasp: An Explanation for Dual Visuomotor Channels in Primate Parietofrontal Cortex - Karl, Jenni M.; Whishaw, Ian Q. (Frontiers in Neurology, 2013)
The Dual Visuomotor Channel Theory proposes that manual prehension consists of two temporally integrated movements, each subserved by distinct visuomotor pathways in occipitoparietofrontal cortex. The Reach is mediated by a dorsomedial pathway and transports the hand in relation to the target’s extrinsic properties (i.e., location and orientation). The Grasp is mediated by a dorsolateral pathway and opens, preshapes, and closes the hand in relation to the target’s intrinsic properties (i.e., size and shape). Here, neuropsychological, developmental, and comparative evidence is reviewed to show that the Reach and the Grasp have different evolutionary origins. First, the removal or degradation of vision causes prehension to decompose into its constituent Reach and Grasp components, which are then executed in sequence or isolation. Similar decomposition occurs in optic ataxic patients following cortical injury to the Reach and Grasp pathways and after corticospinal tract lesions in non-human primates. Second, early nonvisual PreReach and PreGrasp movements develop into mature Reach and Grasp movements but are only integrated under visual control after a prolonged developmental period. Third, comparative studies reveal many similarities between stepping movements and the Reach and between food handling movements and the Grasp, suggesting that the Reach and Grasp are derived from different evolutionary antecedents. The evidence is discussed in relation to the ideas that dual visuomotor channels in primate parietofrontal cortex emerged as a result of distinct evolutionary origins for the Reach and Grasp; that foveated vision in primates serves to integrate the Reach and Grasp into a single prehensile act; and, that flexible recombination of discrete Reach and Grasp movements under various forms of sensory and cognitive control can produce adaptive behavior.